Sea level changes and Neolithic hunter-fisher-gatherers in the centre of Tallinn, southern coast of the Gulf of Finland, Baltic Sea. (July 2017) - Muru, Merle; Rosentau, Alar; Kriiska, Aivar; Lõugas, Lembi; Kadakas, Ulla; Vassiljev, Jüri; Saarse, Leili; Aunap, Raivo; Küttim, Liisa; Puusepp, Liisa; Kihno, Kersti
Relative sea level (RSL) changes and the palaeogeography of a Neolithic hunter-fisher-gatherer settlement site on the former shore of the Gulf of Finland in the city centre of Tallinn were reconstructed by implementing GIS in landscape modelling based on archaeological, sedimentary and shore displacement data. AMS radiocarbon dating of mammal bones from the cultural layer suggests the existence of the hunter-fisher-gatherer settlement around 5.1–4.8 cal. ka BP on a seaward inclining sandy beach of Tallinn palaeo-bay c. 100 m from the Litorina Sea shoreline and at about 2.4 m above the coeval sea level. The shoreline passed the study site at about 5.8 cal. ka BP and retreated towards northeast with an average speed of 13 m per century, while the RSL lowered by c. 2.5 mm annually. Combining radiocarbon dates of terrestrial and marine mammal bones from the Neolithic cultural layer, a marine reservoir effect of 350 14 C years for the brackish-water Baltic Sea was calculated. By using high-resolution archaeological data in combination with RSL and other geological proxies, we demonstrate new possibilities to reconstruct the palaeoenvironment of deeply buried coastal settlement sites and to predict a possible continuation of the cultural layer in heavily built-up areas.